2011
DOI: 10.1039/c1cp21984g
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous oscillations of cell voltage, power density, and anode exit CO concentration in a PEM fuel cell

Abstract: The spontaneous oscillations of the cell voltage and output power density of a PEMFC (with PtRu/C anode) using CO-containing H 2 streams as anodic fuels have been observed during galvanostatic operating. It is ascribed to the dynamic coupling of the CO adsorption (poisoning) and the electrochemical CO oxidation (reactivating) processes in the anode chamber of the single PEMFC. Accompanying the cell voltage and power density oscillations, the discrete CO concentration oscillations at the anode outlet of the PEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…From a technical point of view, the occurrence of oscillatory kinetics can be thought of as an autonomous self‐cleaning process that can prevent the anode becoming completely poisoned by adsorbed carbon monoxide, as is the case under conventional, non‐oscillatory conditions. In fact, it has been reported that operating a fuel cell under an oscillatory regime can result in higher average power densities than those obtained at a steady state …”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…From a technical point of view, the occurrence of oscillatory kinetics can be thought of as an autonomous self‐cleaning process that can prevent the anode becoming completely poisoned by adsorbed carbon monoxide, as is the case under conventional, non‐oscillatory conditions. In fact, it has been reported that operating a fuel cell under an oscillatory regime can result in higher average power densities than those obtained at a steady state …”
Section: Introductionsupporting
confidence: 71%
“…It can be seen that the differences between the Pd‐Pt/C and Pd/C systems studied herein, and their differences relative to the Pt‐Ru/C system, which is widely discussed in the literature, reflect different adsorption/oxidation kinetic constants of CO and of H 2 , in addition to the H 2 O dissociation on the catalyst surface for the formation of OH ad . As first proposed by Lopes et al., CO‐stripping voltammetry can be used to estimate the mean amplitude of oscillation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pd1 catalyst is the only catalyst that exhibits spontaneous oscillations of the fuel cell potential. These oscillations may be explained as follows [46]: electrooxidation of impurities of the formic acid to CO ads strongly adsorbed on Pd surface causing the decrease of the FC voltage and power, but at sufficiently low voltage the rate of oxidation of CO ads to CO 2 increases cleaning the surface of the catalyst what results in an increase of FC voltage and power. The other explanation may be that formic acid is directly electrooxidised to CO 2 , which is periodically removed from the catalyst layer [10].…”
Section: Fuel Cell Testsmentioning
confidence: 99%
“…Instabilities, such as these oscillations are quite common in electrochemical systems when there are competing reactions. Several studies have reported spontaneous potential oscillations recorded for PEM PtRu anodes exposed to H 2 and CO. [15][16][17][18] The frequency of such oscillations has been shown to depend on conditions such as current density, gas mixture composition, cell temperature, and gas flow velocity. To our knowledge, this is the first report of current oscillations in a CO 2 /H 2 on PEM PtRu anodes.…”
Section: Resultsmentioning
confidence: 99%